SDGs Value and Islamic Philantrophy Through Zakah Institution During the Covid-19 - Yudha, Ana Toni Roby Candra; Awwaliah, Habibah; Pertiwi, Eka Mega (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2021)
Introduction to The Problem: The mission of the zakat institution as a philanthropic booster is very necessary. As an economic empowerment for the poor and to support micro businesses. Especially when the covid 19 pandemic condition requires a wealth distribution of income and consumption from the sufficient in the weak economy condition.Objective Study: The aims of this study is to identify the optimization of the zakat institution program which involves poverty reduction and the utilization of the poor and disadvantaged. This is in line with SDG’s 1 and 8 values on poverty reduction and the provision of decent work.Methodology: This study uses an explanatory qualitative approach. A solution review of the process of managing and utilizing money waqf at LAZ Yatim Mandiri, using primary data by in-depth interviews with waqf doers and continued with source triangulation, focus group discussion that talks about covid 19 in many perspective, accompanied by the opinion of 15 academicians and 4 experts (fiqh) waqf.Findings: The result of this study showed that the potential for endowments must be balanced with increasing Nazir awareness and understanding to manage endowments of money in order to continue to be useful. Ascertaining the direction of philanthropic movements during pandemic to collect funds and distribute them to the poor and pandemic affected victims is a crucial point. The important advice that LAZ should make is to maintain the intensity of friendship with muzakki or donors and the needy, to create a socially oriented business and also can be appropriate and feasible with the propaganda method used. this needs to be done considering that in addition to humanity issues, other issues that have a severe impact on the covid pandemic 19 are the microeconomic sector and MSME.